RETRACTED: Motivation of English oil and gas terms with a zoonym component - Semenova Marina; Tertychnaia Sofia; Jinhui Jiang (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001